Populism Put to the Polarisation Test: The 2019–20 Election Cycle in Italy. Issue 3 (1st October 2020) - Tronconi, Filippo; Valbruzzi, Marco
ABSTRACT: One year after the birth of an unprecedented government characterised by the strong populist stance of both coalition partners (M5S and the Lega) and amid a growing polarisation in party positions on a number of political issues, the European and regional elections of 2019–20 marked an important test for Italy. After presenting the results of the 2019–20 election cycle, the article investigates the most salient lines of party competition and the varying degrees of polarisation. Our analysis shows two kinds of polarisation: the first being the intra-coalitional polarisation which characterised the first Conte government; while the second, affecting the party system as a whole, is driven by the electoral rise of far-right parties.